2013
DOI: 10.3109/08880018.2013.796025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fatal Cases of Pandemic Influenza A (H1N1) Virus Infections in Pediatric Patients with Leukemia

Abstract: Pandemic H1N1 influenza virus caused mortality in patients with ARDS or HLH; an unexpected finding for pandemic H1N1 (2009) influenza virus. Thus, for children with leukemia and infected with H1N1 virus, short- and long-term complications should be kept in mind during evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…Secondary bacterial or fungal pulmonary infection was the most common complication, occurring in those with RSV (7 patients), the 2009 pandemic H1N1 influenza A (2 patients), and RSV‐influenza B coinfection (1 patient) and progressing to multiorgan failure and a fatal outcome in 1 patient. The complicated viral LRTI described in the current study was in agreement with previous studies that evaluated the severity of RSV‐related and influenza‐related clinical courses in immunocompromised children with cancer . It is important to note that despite the seemingly high rate of complications, the mortality rate was 0.7%, which is at the lower end of the pediatric fever and neutropenia‐related mortality range, which has been reported as 0.5% to 6.6% …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Secondary bacterial or fungal pulmonary infection was the most common complication, occurring in those with RSV (7 patients), the 2009 pandemic H1N1 influenza A (2 patients), and RSV‐influenza B coinfection (1 patient) and progressing to multiorgan failure and a fatal outcome in 1 patient. The complicated viral LRTI described in the current study was in agreement with previous studies that evaluated the severity of RSV‐related and influenza‐related clinical courses in immunocompromised children with cancer . It is important to note that despite the seemingly high rate of complications, the mortality rate was 0.7%, which is at the lower end of the pediatric fever and neutropenia‐related mortality range, which has been reported as 0.5% to 6.6% …”
Section: Discussionsupporting
confidence: 90%
“…In their study, 12 of 69 children with leukemia or lymphoma (17%) were reported to develop LRTI, a percentage that was similar to the current study findings of 12% that also included the 2009 pandemic H1N1 influenza A virus. Our experience with 2009 pandemic H1N1 influenza A infection in children with ALL is not different from other reports in oncology patients . Although the majority of immunocompromised patients with 2009 pandemic H1N1 influenza A virus developed a mild course of URTI, a few case reports have described severe morbidity and mortality.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In our study, 2 out of 8 patients had a fatal course (25%) of which 1 developed pneumonia and acute respiratory distress syndrome, and the other developed HLH and died due to secondary infection in the 6 th week of treatment for HLH. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%